The Role of Public Infrastructure Quality, Foreign Direct Investment, Tax Incentives, and Regulatory Efficiency in Driving Regional Economic Growth and Job Creation in Indonesia - Muhammad Zulfan Abdusyakur; Aster Aryati Rakhmasari (Eastasouth Institute, 2025)
This study investigates the role of public infrastructure quality, foreign direct investment (FDI), tax incentives, and regulatory efficiency in driving regional economic growth and job creation in Indonesia. Using a quantitative research design, primary data were collected from 125 respondents representing business actors, investors, and government officials across various regions in Indonesia. The data were measured using a Likert-scale questionnaire and analyzed employing Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The results reveal that public infrastructure quality, FDI, tax incentives, and regulatory efficiency all have significant positive effects on regional economic growth. Furthermore, these factors also directly and indirectly influence job creation, with regional economic growth acting as a partial mediating variable. Among the examined determinants, regulatory efficiency emerges as the strongest driver of regional economic growth, while economic growth itself plays a key role in translating policy interventions into employment opportunities. The findings underscore the importance of integrated development strategies that combine infrastructure investment, investment promotion, effective fiscal incentives, and regulatory reform to achieve sustainable and inclusive regional development in Indonesia.